N6-methyladenosine (m6A) dysregulation contributes to network excitability in temporal lobe epilepsy - Mathoux, Justine; Wilson, Marc-Michel; Srinivas, Sujithra; Litovskich, Gabrielle; Villalba Benito, Leticia; Tran, Cindy; Kesavan, Jaideep; Harnett, Aileen; Auer, Theresa; Sanz-Rodriguez, Amaya; Kh. A.E. Alkhayyat, Mohammad; Sullivan, Mairéad; et al. (JCI insight, 2025)
Analogous to DNA methylation and protein phosphorylation, it is now well understood that RNA is also subject to extensive processing and modification. N6-methyladenosine (m6A) is the most abundant internal RNA modification and regulates RNA fate in several ways, including stability and translational efficiency. The role of m6A in both experimental and human epilepsy remains unknown. Here, we used transcriptome-wide m6A arrays to obtain a detailed analysis of the hippocampal m6A-ome from both mouse and human epilepsy samples. We combined this with human proteomic analyses and show that epileptic tissue displays disrupted metabolic and autophagic pathways that may be directly linked to m6A processing. Specifically, our results suggest that m6A levels inversely correlate with protein pathway activation. Finally, we show that elevated levels of m6A decrease seizure susceptibility and severity in mice. Together, our findings indicate that m6A represents an additional layer of gene regulation complexity in epilepsy and may contribute to the pathomechanisms that drive the development and maintenance of hyperexcitable brain networks.